Education on Dengue Fever Prevention Through The PSN 3M PLUS Program in The Working Area of The Rapak Mahang Tenggarong Health Center - Nugroho, Purwo Setiyo; Utami, Abdiah Rahma; Wardana, Katingka Aprilia; Astuti, Puji; Nurfitriyani, Nurfitriyani (ABDIMAYUDA: Indonesian Journal of Community Empowerment for Health, 2024)
Abstract.Dengue hemorrhagic fever (DHF) is an infectious/transmitted disease caused by the dengue virus, the bite of a female mosquito, Aedes aegypti and Aedes albopictus from patients who have previously been infected with the dengue virus. The number of deaths due to dengue disease reaches 140,000 every year. This makes DHF in Indonesia a serious problem that needs to be addressed immediately because the number of DHF deaths is increasing from year to year. Purpose : the implementation of this educational activity is to control the Aedes aegypti mosquito population so that the transmission of DHF can be prevented or reduced. Method: The method used in this activity is to educate the public through lecture media to implement the 3M PLUS PSN Program using abatement to kill mosquito larvae. Results: Better understanding of dengue fever prevention and the PSN 3M PLUS program which was carried out by distributing abatement's. Conclusion: Education about the prevention of DHF and the implementation of PSN 3M PLUS with the target of the community getting support and good cooperation from various parties. Suggestion: As a recommendation, from this activity the Government, in this case Puskesmas officers, should continue to educate the public and run the PSN 3M PLUS program which is the most effective and efficient effort to prevent dengue fever (DHF). Keywords: Dengue Fever (DHF), PSN 3M PLUS, Education Abstrak. Demam berdarah dengue (DBD) merupakan penyakit infeksi/menular yang disebabkan oleh virus dengue, gigitan nyamuk betina, Aedes aegypti dan Aedes albopictus dari pasien yang sebelumnya telah terinfeksi virus dengue. Jumlah kematian akibat penyakit DBD mencapai 140.000 setiap tahun. Hal ini menjadikan DBD di Indonesia menjadi masalah serius yang perlu segera ditangani karena jumlah kematian DBD semakin meningkat dari tahun ke tahun. Tujuan : di dilaksanakannya kegiatan edukasi ini adalah untuk mengendalikan populasi nyamuk Aedes aegypti sehingga penularan DBD dapat dicegah atau dikurangi. Metode : yang digunakan dalam kegiatan ini adalah edukasi kepada masyarakat melalui media ceramah untuk menerapkan Program PSN 3M PLUS menggunakan abatesasi untuk membunuh jentik nyamuk. Hasil : Lebih memahami tentang pencegahan demam berdarah dan program PSN 3M PLUS yang di lakukan dengan cara pembagian abatesasi. Kesimpulan: Edukasi tentang pencegahan DBD dan pelaksanaan PSN 3M PLUS dengan sasaran masyarakat mendapat dukungan serta kerja sama yang baik dari berbagai pihak. Saran : Sebagai rekomendasi, dari kegiatan ini Pemerintah dalam hal ini petugas Puskesmas agar terus melanjutkan untuk mengedukasi masyarakat dan menjalankan program PSN 3M PLUS yang merupakan upaya paling efektif dan efisien untuk mencegah demam berdarah (DBD).